Design of high performance, low power latches and flip-flops - Shridhar Mubaraq Mishra. (2011)
With the advent of hand-held computing devices that require functionality rivaling the desktop, Low Power, High Performance systems have become the norm rather than the exception. The clocking network with its 20-40% contribution to the overall power dissipation is becoming a major obstacle in implementing these systems. Hence the need for high performance basic sequential elements with low power dissipation is steadily growing. The aim of this project is to develop latches and flip-flops to fulfill this need. Since latches and flip-flops are used to store logic values, the traditional measures of area, speed and power dissipation are not sufficient to access their quality. In this project, a set of quality measures has been developed for these basic sequential elements.